Expression of the Fluoroquinolones Efflux Pump Genes acrA and mdfA in Urinary Escherichia coli Isolates - Sarah M. Abdelhamid; Rania R. Abozahra (Polish Journal of Microbiology, 2017)
Escherichia coli is one of the most frequent causes of urinary tract infections. Efflux system overexpression is reported to contribute to E. coli resistance to several antibiotics. Our aim in this study was to investigate the relation between antibiotic resistance and the expression of the efflux pump genes acrA and mdfA in E. coli by real-time reverse transcription-PCR. We tested the in vitro susceptibilities to 12 antibiotics in 28 clinical isolates of E. coli obtained from urine samples. We also determined the minimum inhibitory concentrations of levofloxacin to these samples. We then revealed significant correlations between the overexpression of both mdfA and acrA and MICs of levofloxacin. In conclusion, we demonstrated that the increased expression of efflux pump genes such as mdfA and acrA can lead to levofloxacin resistance in E. coli. These findings contribute to further understanding of the molecular mechanisms of efflux pump systems and how they contribute to antibiotic resistance.